Studi Tentang Kesulitan Siswa dalam Pembelajaran Sejarah pada Kelas X IPS 3 di SMA Negeri 7 Kerinci - Intan Zair Maisa; Zafri Zafri (Galanggang Sejarah, 2021)
This research was motivated by the many difficulties experienced by students in learning history in class X IPS 3 at SMA Negeri 7 Kerinci. This study aims to determine the indicators of students' difficulties in learning history in class X IPS 3 at SMA Negeri 7 Kerinci, which are indicators that affect students' difficulties in learning history and which indicators are the most dominant that affect students in learning history. This research is a quantitative descriptive study with a questionnaire collection technique consisting of 17 question items which include indicators of learning outcomes obtained that are not in accordance with the learning carried out, learning activities, attitudes, behavior, and emotional symptoms. Subjects in this study consisted of 30 people. Analysis of the data used is descriptive statistical analysis with TCR count and percentage. Based on the results of the study, it turns out that the description of learning difficulties experienced by students in learning history class X IPS 3 at SMA Negeri 7 Kerinci is found in indicators, the results obtained are not in accordance with what is done, learning activities, and attitudes. The average level of achievement of respondents above 60% is in the high category, namely on items, students rarely do history learning outside school, students rarely complete assignments from the teacher properly and correctly, students rarely do resume assignments given by the teacher on time, students are not happy to make assignments given by the teacher, students rarely answer questions from the teacher when the learning process takes place and students rarely ask the teacher when there is learning material that has not been understood.